Studies on the antioxidant mechanisms of betacyanins from improved fermented red dragon fruit (Hylocereus polyrhizus) drink in HepG2 cells - Lim, Teck Wei; Lim, Renee Lay Hong; Pui, Liew Phing; Tan, Chin Ping; Ho, Chun Wai (Elsevier, 2024)
Red dragon fruit (RDF, Hylocereus polyrhizus) is high in betacyanins content but is understudied for its antioxidant mechanisms in liver cells. The present study aimed to investigate the antioxidant mechanisms of the stabilised betacyanins in a novel RDF functional drink, Improved-FRDFD-dH2O (produced from mild, sustainable approaches) using HepG2 cell line. Results revealed the betacyanins of Improved-FRDFD-dH2O (12.5% and 25%, v/v) showed the highest direct scavenging effect on intracellular ROS from 75.39% to <31%. The antioxidant enzymes (SOD, CAT and GPx) activities in HepG2 cells were remarkably increased, with 12.5% and 25% Improved-FRDFD-dH2O demonstrating the greatest enhancing effects. RT-qPCR proved the betacyanins of Improved-FRDFD-dH2O possessed indirect antioxidant mechanisms, where the gene expressions associated with Nrf2-ARE pathway were upregulated by all the tested sample concentrations (highest fold: 6.82). Overall, the present findings highlighted the RDF's potential in functional product development with betacyanins as the prominent bioactive compound to provide direct and indirect antioxidative and hepatoprotective activities. © 2024 Elsevier B.V.